Equine colic referred to University Veterinary Hospital, Universiti Putra Malaysia from 2005-2011 - Adamu, Lawan; Mohd Adzahan, Noraniza; Abdullah, Rasedee; Fateh Mohamed, Bashir Ahmad (International Organization of Scientific Research, 2012)
Equine colic has been a devastating endemic disease condition confronted by horse owners in Malaysia. However, little attention is paid to the management aspect of these horses and the prevalence of colic. Therefore, this study was conducted to determine the relationship between colic cases and horse usages, gender, breed, management system of establishments and the status of horses. Data were obtained from the University Veterinary Hospital, Universiti Putra Malaysia particularly from the equine and pathology units from January 2005 to December, 2011. Of the 92 number of horses studied for colic cases referred to the hospital, 40% were both stallions and mares respectively while 20% were geldings. 42% were used for patrolling, 18% for multipurpose, 14% were used for endurance followed by 10% for riding school, while 7% were used for both leisure ride and polo respectively and the least 2% were used for dressage. Three types of colic disease conditions were diagnosed and treated and these include tympanic (66%), spasmodic (23%) and impaction (11%) colic. Thus, these findings could assist veterinarians engrossed in the diagnosis and treatment of the conditions to put in place laudable measures in the prevention of the disease conditions.